Espaço urbano e comunicação - Zagui, Paula Apolinário (2018)
This is a study about São Paulo urban space, particularly Paulista Avenue that aims to analyze communicative actions that happen in the urban space focusing on mediation and confrontation with this city eminently interactive. The central question of the research is “in what way does communication interfere in the articulation of urban space and change it into a city”? There is an epistemological distinction between urban space and city considering the difference between a planned and articulated space by the State and an experienced place by the citizens. In this sense, it investigates communication presents in the continuum dialog between Public Power planned space and experienced space. This research intends to use, to comprehend this object, theories related to the urban space production mainly Milton Santos (1997) and Richard Sennett (2015). As methodological strategy, it uses dérive from Debord (1958), that means walking by the city without a defined route and enjoy deviances and unexpectedness experiences the way suggests. Paulista Avenue dérive aims to comprehend how urban space presents visually itself and trespass it to find its visibility to create knowledge about itself. In addition to this, comparison and association about the ways of the people to act in the spaces, can bring an understanding about city and its political and communicative dimension